Interpersonal Care Activities and Brand Equity Increase Patient Response at Type B Hospitals in Bekasi - Irma Nurfauzia; Ratna Indrawati; Sandra Dewi (Majapahit Journal of Islamic Finance and Management, 2026)
This research is based on the results of initial observations, which found that 67% had problems related to Patient Response, of which 80% had problems regarding Customer Loyalty, where patients were reluctant to recommend Type B Hospitals in Bekasi to others on social media. The purpose of this study was to analyze the simultaneous influence of social media marketing activities, interpersonal care activities, and hospital brand equity on the responses of non-insured patients at Type B Hospitals in Bekasi. This research method was quantitative with a cross-sectional design. The population in this study was all non-insured outpatients and inpatients who visited or received treatment at Type B Hospitals in Bekasi. The minimum sample size in this study was 101 respondents. The data collection technique used a questionnaire, and the analysis method used the three-box method and SEM-PLS. The results showed there is an influence of simultaneous social media marketing activities, interpersonal care activities, and hospital brand equity on patient responses. Social media marketing activities and interpersonal care activities have an impact on responding to patients with hospital brand equity as intervening variables.